2010
DOI: 10.1002/adma.200902329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Device Geometry on Sensor Characteristics of Planar Organic Electrochemical Transistors

Abstract: The response of PEDOT:PSS planar electrochemical transistors to H2O2 can be tuned by varying the ratio between the areas of the channel and the gate electrode. Devices with small gates show lower background signal and higher sensitivity. The detection range, on the other hand, is found to be rather independent of the gate/channel area ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
150
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 27 publications
9
150
0
Order By: Relevance
“…The gate voltage modulates the current flowing in the channel between the source and drain electrodes. 12,13 OECTs have been used as sensors for chemical and biological species, such as hydrogen peroxide, 14 glucose, 15 neurotransmitters, 16 chloride ions, 11 DNA, 17 as well as to establish controlled cell gradients on conducting polymer surfaces, 18 monitor tissue integrity, 19 and record in vivo brain activity. 20 They have been integrated with microfluidic channels for lab-on-a-chip applications, 21 and are also the fundamental unit of other newly emerging devices, such as ion transistors and organic electronic ion pumps.…”
mentioning
confidence: 99%
“…The gate voltage modulates the current flowing in the channel between the source and drain electrodes. 12,13 OECTs have been used as sensors for chemical and biological species, such as hydrogen peroxide, 14 glucose, 15 neurotransmitters, 16 chloride ions, 11 DNA, 17 as well as to establish controlled cell gradients on conducting polymer surfaces, 18 monitor tissue integrity, 19 and record in vivo brain activity. 20 They have been integrated with microfluidic channels for lab-on-a-chip applications, 21 and are also the fundamental unit of other newly emerging devices, such as ion transistors and organic electronic ion pumps.…”
mentioning
confidence: 99%
“…One of the most relevant features is the recently proven field-effect enhanced selectivity that allows for chiral differential detection at unprecedented low concentrations (18). OFET sensors can also work in water (19,20) as well as in the subvolt bias regime (20,21). Specificity relies on device structures that either involve enzymatic reactions [with FET electrochemical transduction (22)] or two-layer architectures, including a bioactive film deposited on top of the channel organic semiconductor (18,23,24).…”
mentioning
confidence: 99%
“…The wide stripe was used as the transistor's channel and the narrow one as the gate electrode, as it has been shown that for enzymatic sensing the area of the channel must be larger than that of the gate electrode. 27 A monolayer of 25 (tridecafluoro-1,1,2,2-tetrahydrooctyl) trichlorosilane (FOTS) was patterned on the surface of the device leaving uncovered only a small area of the channel and of the gate electrode. These areas of PEDOT:PSS which were left uncovered by FOTS served as hydrophilic "virtual wells" 28 and were shown 30 to be effective in confining the RTIL (and the glucose solution, when it was added) over the centre of the device.…”
mentioning
confidence: 99%